Gender Equality in Education: A Systematic Analysis of Educational Equity Between Males and Females in Southeast Asia - Joshua , Joshua; Neri, Mario (PT. Batari Edu Calya, 2025)
Gender equality in education remains a critical issue within the Southeast Asian context, where sociocultural diversity and economic disparities contribute to uneven educational access and outcomes. This study employs a Systematic Literature Review (SLR) method, synthesizing research published between 2018 and 2024 from Scopus, SpringerLink, and Google Scholar databases. Findings reveal that while gender parity has largely been achieved at the primary education level, significant disparities persist at the secondary and tertiary levels, particularly in rural areas of Indonesia, Laos, and Cambodia. Cultural norms, patriarchal values, and socioeconomic constraints remain dominant barriers to educational participation among females. Furthermore, gender-based differences in academic achievement are evident, with females outperforming males in literacy while lagging in mathematics and science. Regional initiatives, such as Malaysia’s STEM for Girls Program and Vietnam’s Gender-Responsive Education Policy, demonstrate promising outcomes in narrowing gender gaps through inclusive pedagogical practices and mentorship programs. The study concludes that gender-responsive educational frameworks, community engagement, and teacher training are pivotal to achieving sustainable gender parity in education. Strengthening these measures is essential for promoting social and economic development aligned with the Sustainable Development Goals (SDGs) 4 and 5.